(untitled) (Journal of the College of Basic Education, 2023)
A new mixed ligand complexes were prepared from 2-hydroxy benzylidene-N-(3-carboxyl phenyl) amine and 2-amino pyrimidine with Mn(II),Fe(II),Co(II),Ni(II) and Cu(II).The prepared complexes were characterized by element analysis, FTIR spectroscopy, Uv-vis spectroscopy, magnetic susceptibility and conductivity measurements. From the spectral measurements. From the above data ,the proposed molecular structure for the complexes are tetrahedral geometry. The Structure geometries of these compounds were also suggested in gas phase by using theo retical treatment , using Hyper chem.-6 program through the molecular mechanics and semi-empirical calculations .The heat of formation(∆Hfo) and binding energy(∆Eb) for the free ligands and its metal complexes were calculated by PM3 methods.